The Training of Renewable Energy Systems: Undergraduate Studies - (:unkn) unknown (My University, 2017)
0

As in all over the world, interest in usage of renewable energy sources has increased in Turkey. Due to intersection of universities leadership on the research and the technology field with the renewable energies innovative feature, it is convenient to provide these provide renewable energy trainings in higher education. To provide practical training to have qualified personnel, new laboratories are required to be established in this field. Therefore, it is becoming extremely important to provide practical training in the field of renewable energy at undergraduate and postgraduate level in universities. In this study, practical working example is provided the scope of has been established in technical equipment of the renewable energy laboratory within Marmara University Faculty of Technology Electric Electronic Engineering Department. This study intends to provide guidance to further studies in renewable energy education
Keywords: Mühendislik, Elektrik ve Elektronik